Pharmacological Studies on Tildipirosin in Calves - Magdy, Hadeer; El-Diasty, Mohamed; Rasheed, Nesma; Gabr, Elsayed M. (Journal of Advanced Veterinary Research, 2023)
Bovine respiratory disease (BRD) is the primary health problem in the beef cattle industry worldwide. Tildipirosin was injected as a metaphylaxis to healthy animals and also as a therapeutic to the clinically diseased animal at a dose of 4 mg/kg B.W. TD is effective in reducing the mortality rate and increasing the recovery rate from P. multocida infection which induces damage to the bronchioles and alveoli with fibrinopurulent bronchopneumonia represented by dilated bronchiole with caseated material in its lumen associated with severe leukocytic cells infiltration in the wall, multifocal areas of necrosis organized exudate infiltrated with many neutrophils in alveoli. PCR is considered the test of choice in the diagnosis of Pasteurella as it can identify organisms at any level regardless of tiny quantities of bacteria’s genome, consequently, the sensitivity and specificity of the test increased. Tildipirosin injection caused no significant changes in RBC count after treatment for the treated healthy and treated diseased group compared with the control group. Tildipirosin showed no significant changes in hemoglobin content and HCT of the treated healthy group but a significant decrease in TD treated diseased group was revealed post-treatment compared to the control group. Single subcutaneous injection of Tildipirosin causes an important decrease in MCV, and MCH levels in TD treated diseased group and decreasing in the MCHC of TD treated healthy group at day 7 compared to the control group. Tildipirosin causes no significant changes in Malondialdehyde (MDA) levels in TD-treated healthy while it increased in the TD-treated diseased group at all days after treatment compared to the control group. No significant changes occur in the superoxide dismutase (SOD) level of TD treated healthy group and TD treated diseased group compared to the control group. In conclusion, p. multocida is one of the most prevalent causes of BRD in Egypt, and tildipirosin was highly effective as a prophylactic and metaphylactic treatment against BRD cases caused by p. multocida, and it has a potentially anti-inflammatory effect.